Welding flux for submerged-arc welding of P91 steel and production method of welding flux
By developing a flux for submerged arc welding of P91 steel that regulates the alkalinity, viscosity and wetting of slag, the problems of P91 steel being difficult to weld and prone to cold cracks are solved, and excellent process performance and metallurgical properties during welding are achieved, and the impact toughness and low hydrogen content of weld metal are improved.
Patent Information
- Application Number
- CN202411941451.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-25
AI Technical Summary
P91 steel welding has problems such as high difficulty, easy to produce cold cracks, difficult to ensure the toughness of weld metal, and easy to stick to slag, and it is difficult to balance the welding slag removal performance and metallurgical performance.
A flux for submerged arc welding of P91 steel was developed. By adjusting the alkalinity, viscosity and wettability of the slag, it uses magnesite, mullite, marble, fluorite, rare earth, rutile and titanium dioxide composite materials, high-carbon iron manganese, etc., and combined with specific production methods, a flux with excellent welding process performance and welding metallurgy performance was prepared.
It achieves good operability during welding, and obtains good welding process performance and welding metallurgy performance, including good slag removal, weld molding, suppression of welding cracks and pores, while improving the impact toughness of weld metal and the ultra-low diffused hydrogen content of the deposited metal.
Smart Images

Figure CN119870788A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of welding materials, in particular to a flux for P91 steel submerged arc welding and a production method thereof. Background Art
[0002] P91 steel is an improved 9Cr-1Mo steel. It is a new generation of heat-resistant martensitic steel developed on the basis of 9Cr-1Mo steel by controlling the content of C, N, Al, Mo, Cr, Mn, and Si elements, adding alloy elements such as V and Nb, and adopting purification and fine grain metallurgical technology, as well as microalloying and controlled rolling and controlled cooling processes. It has high high-temperature creep rupture strength, low thermal expansion, good thermal conductivity, good processability and oxidation resistance.
[0003] However, when welding the weld joint with welding materials, it is different from steel smelting, which is a "small metallurgical" process with limited area heating. The weld metal cannot be subjected to controlled rolling and deformation heat treatment like steel, and the grains cannot be refined. P91 steel is a medium-high alloy with a total alloy element content of more than 13%, which leads to an increase in Ms point, so that the weld structure will obtain martensite even under air cooling conditions, resulting in a large tendency to harden and strong cold crack sensitivity. The carbon equivalent Ceq>2.2% (steel with Ceq≤0.45% has good weldability) and poor weldability. Nb, V, etc. are added to the parent material, which leads to easy sticking or inclusion of slag in the welding rod or submerged arc welding during joint welding. Therefore, the welding of P91 steel has the difficulties of high welding requirements, high difficulty, easy to produce welding cold cracks, difficult to ensure the toughness of the weld metal, easy to stick slag, etc. It is a great challenge in welding material design to balance the welding slag removal performance and metallurgical performance, and balance the anti-porosity, anti-crack performance and welding slag removal performance.
[0004] Submerged arc welding is an important means of welding P91 steel. The comprehensive performance of submerged arc welding flux often determines the welding efficiency and the final welding quality, which requires the submerged arc welding flux to have both good welding process performance and welding metallurgical properties. Summary of the invention
[0005] The purpose of the present invention is to provide a flux for submerged arc welding of P91 steel and a production method thereof. By adjusting the basicity, viscosity and wettability of the slag, a flux is developed. When used for welding P91 steel, the flux has good operability and can obtain good welding process performance, including good slag removal and weld formation, effective suppression of welding cracks and pores, and at the same time, a weld metal with good impact toughness can be obtained, and the deposited metal has an ultra-low diffusible hydrogen content (2.5-3.5) ml / 100g. The problem of localized submerged arc welding of P91 steel is solved.
[0006] To achieve the above object, the present invention provides the following technical solution: A flux for submerged arc welding of P91 steel, comprising the following components by mass fraction:
[0007] Magnesite: 16.2%-24.8%; Mullite: 18.2%-27.9%; Marble: 28.2%-37.2%; Fluorite: 14.2%-20.8%; Rare earth: 1.15%-1.55%; Rutile and titanium dioxide composite material: 1.15-6.25%; High carbon ferromanganese: 1.10%-1.4%.
[0008] Preferably, the following components are included by mass fraction:
[0009] Magnesite: 19.3%; Mullite: 27.9%; Marble: 35.2%; Fluorite: 14.2%; Rare earth: 1.15%; Rutile and titanium dioxide composite material: 1.15%; High carbon ferromanganese: 1.10%.
[0010] Preferably, the following components are included by mass fraction:
[0011] Magnesite: 17.5%; Mullite: 25.9%; Marble: 30.2%; Fluorite: 20.8%; Rare earth: 1.2%; Rutile and titanium dioxide composite material: 3.2%; High carbon ferromanganese: 1.20%.
[0012] Preferably, the following components are included by mass fraction:
[0013] Magnesite: 21%; Mullite: 23%; Marble: 32%; Fluorite: 20.5%; Rare earth: 1.25%; Rutile and titanium dioxide composite material: 1.15%; High carbon ferromanganese: 1.10%.
[0014] Preferably, the following components are included by mass fraction:
[0015] Magnesite: 22%; Mullite: 19.1%; Marble: 35.19%; Fluorite: 19%; Rare earth: 1.18%; Rutile and titanium dioxide composite material: 2.15%; High carbon ferromanganese: 1.38%.
[0016] Preferably, the following components are included by mass fraction:
[0017] Magnesite: 16.2%; Mullite: 19.5%; Marble: 37.2%; Fluorite: 18%; Rare earth: 1.5%; Rutile and titanium dioxide composite material: 6.2%; High carbon ferromanganese: 1.4%.
[0018] Preferably, the following components are included by mass fraction:
[0019] Magnesite: 24.8%; Mullite: 18.2%; Marble: 28.2%; Fluorite: 19.6%; Rare earth: 1.55%; Rutile and titanium dioxide composite material: 6.25%; High carbon ferromanganese: 1.4%.
[0020] Preferably, a method for producing a flux for submerged arc welding of P91 steel comprises the following steps:
[0021] S1: The magnesite, mullite, marble, fluorite, rare earth, rutile and titanium dioxide composite material and high carbon ferromanganese are mixed evenly in a mixer according to a preset component ratio, and then 2.5 modulus potassium sodium water glass with a concentration of 42% to 45% and a total component amount of 17.5-23.5% is added, and the mixture is stirred evenly and granulated;
[0022] S2: The semi-finished product granulated in step S1 is baked in a baking oven at 150-250° C. for 40 minutes;
[0023] S3: The semi-finished granulated product baked in step S2 is screened using 8-mesh and 40-mesh screens to remove particles other than those of 8 to 40 meshes;
[0024] S4: The particles screened in step S3 are sintered in a high-temperature sintering furnace at 815-855° C. for 40 minutes. After sintering, finer particles are screened out using a sieve to obtain flux.
[0025] Preferably, the basicity of the flux prepared in S4 is 3.2-3.6.
[0026] Preferably, the flux prepared in S4 has a bulkiness of 0.8-1.2 kg / m 3 .
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: in the flux formula design of the present invention, fluoride is added to reduce the hydrogen content of the weld metal by means of HF, and fluorite is the most commonly used fluoride raw material; fluorite has a low melting point of 1375°C and is a strong diluent, which can significantly reduce the melting point of the slag and allow the gas in the weld to escape; fluorite is a highly ionized substance, and adding more than 10% will destroy the arc stability. In the present invention, fluorite is added at 14.2%-20.8%, which effectively reduces the hydrogen content in the deposited metal; CaO produced by the decomposition of fluorite and marble can also reduce the density of the slag, reduce the solubility of heavy metal sulfides in the slag, and reduce the loss of metal in the slag, thereby increasing the transition coefficient of the alloy in the flux to the deposited metal. Rare earth elements such as lanthanum and cerium are added in appropriate amounts to refine the weld structure and improve the plasticity and impact toughness of the weld. The composite fired product of rutile and titanium dioxide in a ratio of 1:1 has weak oxidizability, good thermal slag removal, stable arc, calm molten pool, active slag, effectively reduces the viscosity of slag at high temperature, and has fine weld ripples. The slag evenly covers the weld to protect the weld, and has good directional weldability. Magnesite is used as a slag-making agent to adjust the basicity of the slag and the weld formation, and the addition amount is controlled at 16.2%-24.8%. High carbon ferromanganese 1.10%-1.4% can supplement the C burning loss of the welding wire and adjust the strength and impact toughness of the deposited metal. Mullite reacts with iron oxide in the molten pool in the flux slag system of the present invention to remove the gas in the weld and accelerate the welding speed. The proper addition can increase the activity of the slag. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the production process of the present invention;
[0029] Figure 2 The CaO-Al 2 O 3 -SiO 2 Ternary phase diagram. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] See also Figure 1-2 The present invention provides a technical solution: a flux for P91 steel submerged arc welding, characterized in that it includes the following components by mass fraction:
[0032] Magnesite: 16.2%-24.8%; Mullite: 18.2%-27.9%; Marble: 28.2%-37.2%; Fluorite: 14.2%-20.8%; Rare earth: 1.15%-1.55%; Rutile and titanium dioxide composite material: 1.15-6.25%; High carbon ferromanganese: 1.10%-1.4%;
[0033] According to the above-mentioned range of flux ingredients and method for preparing flux, the component contents in Table 1 are taken and flux is prepared according to the method described in Examples 1-6 described below.
[0034] Table 1 Flux component contents of Examples 1-6
[0035]
[0036] Embodiment 1:
[0037] According to the component contents of Example 1 in Table 1 above, the raw materials were placed in a mixer, stirred and mixed evenly, and then 2.5 modulus potassium sodium water glass accounting for about 20% of the total weight of the powder and having a concentration of 42% was added and mixed, and granulated. The obtained granules were baked at a low temperature of 150-250°C, sintered at a high temperature of (815-855)°C, and sieved to obtain granules with a basicity of 3.4 and a bulkiness of 0.8-1.2 kg / m 3 of flux No. 1.
[0038] Experimental Example 2:
[0039] According to the component contents of Example 2 in Table 1 above, the raw materials were placed in a mixer, stirred and mixed evenly, and then 2.5 modulus potassium sodium water glass accounting for about 23.5% of the total weight of the powder and having a concentration of 42.5% was added and mixed, and granulated. The obtained granules were baked at a low temperature of 150-250°C, sintered at a high temperature of (815-855)°C, and sieved to obtain granules with a basicity of 3.2 and a bulkiness of 0.8-1.2 kg / m 3 Flux No. 2.
[0040] Experimental Example 3:
[0041] According to the component contents of Example 3 in Table 1 above, the raw materials were placed in a mixer, stirred and mixed evenly, and then 2.5 modulus potassium sodium water glass accounting for about 17.5% of the total weight of the powder and having a concentration of 43% was added and mixed, and granulated. The obtained granules were baked at a low temperature of 150-250°C, sintered at a high temperature of (815-855)°C, and sieved to obtain granules with a basicity of 3.5 and a bulkiness of 0.8-1.2 kg / m 3 Flux No. 3.
[0042] Experimental Example 4:
[0043] According to the component contents of Example 4 in Table 1 above, the raw materials were placed in a mixer, stirred and mixed evenly, and then 2.5 modulus potassium sodium water glass with a concentration of 44% accounting for about 18.5% of the total weight of the powder was added and mixed, and granulated. The obtained granules were baked at a low temperature of 150-250°C, sintered at a high temperature of (815-855)°C, and sieved to obtain granules with a basicity of 3.5 and a bulkiness of 0.8-1.2 kg / m 3 Flux No. 4.
[0044] Experimental Example 5:
[0045] According to the component contents of Example 5 in Table 1 above, the raw materials were placed in a mixer, stirred and mixed evenly, and then 2.5 modulus potassium sodium water glass accounting for about 21.5% of the total weight of the powder and having a concentration of 45% was added and mixed, and granulated. The obtained granules were baked at a low temperature of 150-250°C, sintered at a high temperature of (815-855)°C, and sieved to obtain granules with a basicity of 3.3 and a bulkiness of 0.8-1.2 kg / m 3 Flux No. 5.
[0046] Experimental Example 6:
[0047] According to the component contents of Example 6 in Table 1 above, the raw materials were placed in a mixer, stirred and mixed evenly, and then 2.5 modulus potassium sodium water glass accounting for about 19% of the total weight of the powder and having a concentration of 43% was added and mixed, and granulated. The obtained granules were baked at a low temperature of 150-250°C, sintered at a high temperature of (815-855)°C, and sieved to obtain granules with a basicity of 3.6 and a bulkiness of 0.8-1.2 kg / m 3 Flux No. 6.
[0048] Comparative Example:
[0049] According to the component contents of the comparative example in Table 1 above, the raw materials were placed in a mixer, stirred and mixed evenly, and then 3.1 modulus potassium sodium water glass accounting for about 17.5% of the total weight of the powder and having a concentration of 38% was added and mixed, and granulated. The obtained granules were baked at a low temperature of 150-250°C, sintered at a high temperature of (815-855)°C, and sieved to obtain granules with a basicity of 3.8 and a bulkiness of 1.6 kg / m 3 of the comparison flux.
[0050] experiment:
[0051] The test plate is a 25 mm thick Q345 common steel plate, and a P91 steel special welding rod is used for the edge stacking. The flux prepared in the above embodiments 1-6 and the comparative example flux are used in combination with a hydrogen-resistant steel special submerged arc welding wire CHW-S91 for welding test, and the special welding wire composition (by weight percentage) is: C: 0.095%, Mn: 0.56%, Si 0.20%, S 0.003%, P 0.005%, Cr9.8%, Ni 0.56%, Mo8.9%, Cu 0.06%, V 0.21%, Nb 0.052%, and the balance is Fe.
[0052] The flux prepared in Examples 1-6 has excellent welding process, easy slag removal, beautiful weld formation, good straightness, no defects such as pressure pits, slag inclusions, pores, cracks, etc., and the deposited metal has an ultra-low diffusible hydrogen content (2.5-3.5) ml / 100g.
[0053] The flux prepared in the comparative example has poor process and serious slag sticking during welding: due to the high marble content, the hardness of the slag shell is large, the surface corrugations of the weld are coarse and have sharp arcs, the slag viscosity is large, the wettability of the weld edge is poor, the linearity is poor, and the weld is pitted; when welding in the groove, the welding slag is not easy to break and is easily stuck in the groove, the operation is difficult and the welding efficiency is low; the fluorite content is low, resulting in poor wettability of the weld metal, high slag viscosity, an unrounded weld transition, and easy inclusions and unfusion; the manganese alloy content is low, the weld strength cannot meet the design requirements, and the molten pool is insufficiently deoxidized, the weld surface is oxidized and appears blue, the S removal is insufficient, and the S content of the deposited metal increases.
[0054] According to the relevant national testing standards, the performance of the welds was tested and the test results shown in Table 2 were obtained:
[0055] Table 2 Mechanical properties test results of Examples 1-6
[0056]
[0057] In Table 2 above, the tensile strength refers to the tensile strength of the welded joint.
[0058] In the 6 groups of welding experiments described in this specification, the arc is stable and the slag removal is good during welding, the weld performance is stable, the S, P, impurity content and diffusible hydrogen content are low, and there is good resistance to hydrogen-induced cracking and sulfide stress corrosion.
[0059] The flux of the present invention is used for welding under the P91 steel welding process, and the weld after welding has low S and P similar to the P91 steel body, low diffusible hydrogen content, high basicity design, good cold crack resistance and good toughness, etc.; the weld metal with beautiful weld shape and no defects such as slag inclusion, pressure pits, and pores is obtained.
[0060] Specifically, viscosity is one of the important properties of slag. It is closely related to the heat and mass transfer rate of the molten pool. The slag must have appropriate viscosity during the welding process to ensure normal operation and obtain high-quality molten pool metal and weld formation. The molten pool of overly sticky slag is inactive, and the liquid metal reaction in the molten pool cannot be fully carried out. Overly thin slag is easy to cause arc irritability, and O in the air 2 、N 2 Intrusion is not conducive to the protection of the molten pool metal and the formation of the weld. There are many factors that affect the viscosity: the high melting point of the slag, the large amount of undissolved solid particles such as CaO and MgO, and the large amount of complex large ion groups will cause the viscosity to increase sharply. During welding, the average temperature of the molten pool is about 1700℃, the viscosity of the liquid metal is about 0.0025Pa·s, the normal slag viscosity is 0.02~0.10Pa·s, the thin slag viscosity is 0.002Pa·s, and the thick slag viscosity is greater than 0.20Pa·s. The viscosity of the slag is about 1 times greater than that of the molten steel. Usually, the melting point of the slag is lower than that of the liquid metal to ensure that the slag has good fluidity and responsiveness when the molten pool is liquid.
[0061] The temperature and basicity of the slag have a great influence on its viscosity. When the temperature is 1600-1650℃ and the basicity is 1.8-4.2, its viscosity is between 0.03-0.07Pa·s. For slag with high basicity, its viscosity increases sharply as the temperature decreases. This is because high melting point 2CaO and SiO are precipitated from the slag. 2 The viscosity of acidic slag with basicity below 0.9 is higher than that of alkaline slag because it contains a large number of large ion groups (SiO 4 ) 4- 、(si 2 O 7 ) 6- 、(Si 6 O 18 ) 12- , but when the temperature decreases, the viscosity increases steadily, and this slag is called long slag. In order to obtain ultra-low hydrogen and good toughness, the flux slag system of the present invention adopts a high basicity design.
[0062] P91 steel is an air-cooled martensitic steel, which is sensitive in structure. Second, during the martensitic transformation after welding, hydrogen remains in the martensite in a supersaturated state, causing further embrittlement of the area. Third, due to the martensitic phase transformation after welding, the structural stress at the joint increases. The combined effect of these three factors makes P91 steel more sensitive to cold cracks. In the development of welding materials, the cold crack sensitivity of the deposited metal can be reduced by controlling the hydrogen content.
[0063] In the flux formula design of the present invention, fluoride is added to reduce the hydrogen content of the weld metal by means of HF. Fluorite is the most commonly used fluoride raw material. Fluorite has a low melting point of 1375°C and is a strong diluent. It can significantly reduce the melting point of the slag and allow the gas in the weld to escape. Fluorite is a highly ionized substance. Adding more than 10% will destroy the stability of the arc. In the present invention, fluorite is added at 14.2%-20.8%, which effectively reduces the hydrogen content in the deposited metal.
[0064] However, the amount of fluorite added is large, the melting point and viscosity of the slag are low, and due to the unstable arc, a bulge is formed on the weld, which is easy to cause slag inclusion. In the present invention, an appropriate amount of marble with non-high ionization material is added, and the decomposition is stable during arc combustion, and the CO generated is 2 It can balance the HF partial pressure during arc reaction, effectively stabilize the arc, and at the same time combine with S and P in the molten pool to form Ca 3 P 2 O 8 and CaS, floating on the slag to achieve the effect of removing S and P; the melting point is 2572℃, which adjusts the melting point of the slag; the slag formed by marble is short slag, and adding too much increases the viscosity of the slag, the weld is rough, and the welding speed needs to be slowed down. When the ratio of marble to fluorite is greater than 1, the arc is stable, and when it is close to 3, filamentous sticky slag appears in the weld, the slag removal is poor during V-groove welding, the slag is hard and glassy, and the dehydrogenation effect becomes worse. In the present invention, marble is added: 28.2%-37.2%.
[0065] The CaO produced by the decomposition of fluorite and marble can also reduce the density of the slag, reduce the solubility of heavy metal sulfides in the slag, and reduce the loss of metal in the slag, thereby increasing the transition coefficient of the alloy in the flux to the deposited metal.
[0066] Add appropriate amounts of rare earth elements, such as lanthanum and cerium, to refine the weld structure and improve the plasticity and impact toughness of the weld.
[0067] The 1:1 composite fired product of rutile and titanium dioxide has weak oxidizability, good thermal slag removal, stable arc, calm molten pool, active slag, and effectively reduces the viscosity of slag at high temperature. The weld ripples are fine, and the slag evenly covers the weld to protect the weld. It has good directional weldability. Excessive use will seriously reduce the mechanical properties. Addition amount: 1.15-6.25%.
[0068] Magnesite is used as a slag-making agent to adjust the basicity of the slag and the weld formation. The addition amount is controlled at 16.2%-24.8%
[0069] High carbon ferromanganese 1.10%-1.4% can supplement the C burning loss of welding wire and adjust the strength and impact toughness of deposited metal.
[0070] Mullite in the flux slag system of the present invention reacts with the iron oxide in the molten pool to remove gas from the weld and speed up the welding speed. Adding a proper amount can increase the activity of the slag, while excessive use will increase the viscosity of the slag. Al2O3 has the function of increasing the surface tension of the slag and is an adjuster of the slag viscosity. Through a large number of experimental comparisons, adding a certain amount of mullite can reduce pressure pits and the tendency to produce pressure pits, but too high a content will make the arc of the weld sharper and less smooth, and easily produce pores and pitting, and the slag shell will become hard. Too low a content will make the weld surface uneven, and defects such as pressure pits and undercuts will appear, affecting the formation of the weld. Therefore, the amount of mullite added is controlled at (21-30)%, according to Figure 2 CaO-Al 2 O 3 -SiO 2 Ternary phase diagram, in the ratio of the present invention, the composition of the slag is located in the region of the ternary low eutectic point and has a lower melting temperature.
[0071] The present invention is based on a large number of repeated experiments and researches, and it is found that when the formula composition of the flux and the sintering process are limited within a specific range, the basicity of the flux can be controlled to be 3.2-3.6, and the bulk density can be controlled to be 0.8-1.2 kg / m 3 , which can better balance the metallurgical properties of the flux and the welding process performance, and obtain ultra-low hydrogen weld metal and good impact toughness, thereby solving the above-mentioned problems, and thus completing the present invention.
[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A flux for submerged arc welding of P91 steel, characterized in that: The following components are included by mass fraction: Magnesite: 16.2%-24.8%; Mullite: 18.2%-27.9%; Marble: 28.2%-37.2%; Fluorite: 14.2%-20.8%; Rare earth: 1.15%-1.55%; rutile and titanium dioxide composite material: 1.15-6.25%; high carbon ferromanganese: 1.10%-1.4%.
2. A flux for submerged arc welding of P91 steel according to claim 1, characterized in that: The following components are included by mass fraction: Magnesite: 19.3%; Mullite: 27.9%; Marble: 35.2%; Fluorite: 14.2%; Rare earth: 1.15%; rutile and titanium dioxide composite material: 1.15%; high carbon ferromanganese: 1.10%.
3. A flux for submerged arc welding of P91 steel according to claim 1, characterized in that: The following components are included by mass fraction: Magnesite: 17.5%; Mullite: 25.9%; Marble: 30.2%; Fluorite: 20.8%; Rare earth: 1.2%; rutile and titanium dioxide composite material: 3.2%; high carbon ferromanganese: 1.20%.
4. A flux for submerged arc welding of P91 steel according to claim 1, characterized in that: The following components are included by mass fraction: Magnesite: 21%; Mullite: 23%; Marble: 32%; Fluorite: 20.5%; Rare earth: 1.25%; rutile and titanium dioxide composite material: 1.15%; high carbon ferromanganese: 1.10%.
5. A flux for submerged arc welding of P91 steel according to claim 1, characterized in that: The following components are included by mass fraction: Magnesite: 22%; Mullite: 19.1%; marble: 35.19%; fluorite: 19%; rare earth: 1.18%; rutile and titanium dioxide composite material: 2.15%; high carbon ferromanganese: 1.38%.
6. A flux for submerged arc welding of P91 steel according to claim 1, characterized in that: The following components are included by mass fraction: Magnesite: 16.2%; Mullite: 19.5%; Marble: 37.2%; Fluorite: 18%; Rare earth: 1.5%; rutile and titanium dioxide composite material: 6.2%; high carbon ferromanganese: 1.4%.
7. A flux for submerged arc welding of P91 steel according to claim 1, characterized in that: The following components are included by mass fraction: Magnesite: 24.8%; Mullite: 18.2%; Marble: 28.2%; Fluorite: 19.6%; Rare earth: 1.55%; rutile and titanium dioxide composite material: 6.25%; high carbon ferromanganese: 1.4%.
8. The method for producing a flux for submerged arc welding of P91 steel according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: The magnesite, mullite, marble, fluorite, rare earth, rutile and titanium dioxide composite material and high carbon ferromanganese are mixed evenly in a mixer according to a preset component ratio, and then 2.5 modulus potassium sodium water glass with a concentration of 42% to 45% and a total component amount of 17.5-23.5% is added, and the mixture is stirred evenly and granulated; S2: The semi-finished product granulated in step S1 is baked in a baking oven at 150-250° C. for 40 minutes; S3: The semi-finished granulated product baked in step S2 is screened using 8-mesh and 40-mesh screens to remove particles other than those of 8 to 40 meshes; S4: The particles screened in step S3 are sintered in a high-temperature sintering furnace at 815-855° C. for 40 minutes. After sintering, finer particles are screened out using a sieve to obtain flux.
9. The method for producing a flux for submerged arc welding of P91 steel according to claim 8, characterized in that: Features: The basicity of the flux prepared in S4 is 3.2-3.
6.
10. The method for producing a flux for submerged arc welding of P91 steel according to claim 8, characterized in that: The flux prepared in S4 has a bulkiness of 0.8-1.2 kg / m 3 .